Event related desynchronisation predicts functional propriospinal myoclonus. (October 2016) - Meppelink, A.M.; Little, S.; Oswal, A.; Erro, R.; Kilner, J.; Tijssen, M.A.J.; Brown, P.; Cordovari, C.; Edwards, M.
Abstract: Objective: Recent diagnostic criteria for functional movement disorders have proposed a "laboratory supported" level of diagnostic certainty where the clinical diagnosis is supported by a positive test. For functional myoclonus the Bereitschaftspotential (BP) is generally accepted as a positive laboratory test. We hypothesised that a different EEG measure, event-related desynchronisation (ERD), might be more effective. Methods: We analysed 20 patients with functional propriospinal myoclonus (fPSM) and 9 controls with organic myoclonus and performed back-averaging for BPs plus time-frequency decomposition to assess ERD and calculated sensitivity and specificity for both techniques. Results: The BP was present in only 25% of patients with fPSM while the majority showed a significant ERD (mean 38 Hz; sensitivity 65%). ERD was significant at the group level (p < 0.001), but not the BP (p > 0.05). Both BP and ERD were absent in our control group. Conclusion: ERD in high-beta may be a useful new test for positive diagnosis of functional myoclonus. Highlights: Event-related desynchronisation (ERD) occurs in the majority of patients with functional propriospinal myoclonus. ERD may be a useful new test for positive diagnosis of functional myoclonus. The finding of ERD prior to functional myoclonic jerks is predicted by the attention based model of functional neurological disorders recently proposed.